Yvonne (Rorke) Pratt - Rorke Family (1941)
Cataloguer's title. Yvonne (Rorke) Pratt (1922-1998), youngest child of Kathleen (Forward) Rorke and James Rorke, was born on 4 June 1922. She was the granddaughter of James Addy Rorke and Ernest Edward Forward. Yvonne married Ewart A. Pratt (1919-2000), son of Calvert Coates Pratt and Agnes (Horwood) Pratt, on 30 October 1943 and had two children: Kathleen Agnes (Pratt) LeGrow and James Rorke Pratt (1949-2000). Yvonne died on 10 March 1998. The Rorke Family Photograph Collection contains 301 black and white and 28 colour photographs of the Rorke Family of Carbonear, Newfoundland, as well as the Forward and Bemister families from that area who are linked to it by marriage. Although spanning from the 1840s-1970s, most photos are from 1900-45, showing family events, homes and Newfoundland and Labrador locations. There is also an album of photos taken while James Rorke attended the Leys School in Cambridge, England.